simplify -8 (5b + 2) - 7 (b-5)

1 answer

To simplify the expression -8(5b + 2) - 7(b-5), we will first distribute the -8 and -7 to the terms in the parentheses:

-8(5b + 2) - 7(b-5) = -40b - 16 - 7b + 35

Combining like terms, we get:

-40b - 16 - 7b + 35 = -47b + 19

Thus, the simplified expression is -47b + 19.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions